2014
DOI: 10.1002/cam4.177
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of antiangiogenic treatment responses in a mouse xenograft tumor model using quantitative perfusion MRI

Abstract: Angiogenesis plays a major role in tumor growth and metastasis, with tumor perfusion regarded as a marker for angiogenesis. To evaluate antiangiogenic treatment response in vivo, we investigated arterial spin labeling (ASL) magnetic resonance imaging (MRI) to measure tumor perfusion quantitatively. Chronic and 24-h acute treatment responses to bevacizumab were assessed by ASL and dynamic-contrast-enhanced (DCE) MRI in the A498 xenograft mouse model. After the MRI, tumor vasculature was assessed by CD34 stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
1
14
1
Order By: Relevance
“…Studies with anti‐angiogenic treatments have shown reduction of perfusion and microvascular density in mice . In our study, perfusion was not correlated with vessel density or area ratio over the entire tumor.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Studies with anti‐angiogenic treatments have shown reduction of perfusion and microvascular density in mice . In our study, perfusion was not correlated with vessel density or area ratio over the entire tumor.…”
Section: Discussioncontrasting
confidence: 83%
“…It was found that SNR efficiency generally peaked between 5 and 20 pairs of averages and then gradually decreased with more averaging. Therefore, 20 pairs of averages were used in our later tumor studies to optimize the scan time, SNR and quantification accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased tumor perfusion, with only reductions in vessel size/ area has been reported in xenograft cancer models after acute treatment with bevacizumab, whereas vessel density decreased after chronic treatment (42). The doses of the angiogenesis inhibitors-we used a low clinically relevant dose of bevacizumab-and duration of the treatment are likely to account for the different results, in the different experimental settings (13,42,43). Inadequate vasculature and decreased permeability due to wrong timing or too high dose of an antiangiogenics may in Figure 3.…”
Section: Resultsmentioning
confidence: 93%
“…Perfusion measurements by ASL were able to differentiate renal masses with different histological findings [45] and cellularity [46,47]. In animal models, ASL could follow the response to anti-angiogenic treatments [43,48] and reflected cell viability in tumors responding to sorafenib [49]. In patients, ASL measurements were proposed for evaluating the completeness of tumor ablation and the extent of coagulation regions in RF ablation of RCC [50].…”
Section: Asl Mri In the Assessment Of Kidney Pathologiesmentioning
confidence: 99%